Professional Development for Islamic Religious Education and Madrasah Teacher - Rohmat Mulyana; Opik Taupik Kurahman; Reza Fauzi (Jurnal Pendidikan Islam, 2023)
In Indonesia, PPG (Pendidikan Profesi Guru/Teacher Professional Development) program is designed for in-service teachers to develop their competence and professionalism to meet national education standards. This program requires participating teachers to take UKMPPG (Uji Kompetensi Mahasiswa Pendidikan Profesi Guru/Competence Test for Teacher Professional Development) which covers both UP (Uji Pengetahuan/Knowledge Test) and UKIN (Uji Kinerja/ Performance Test). This study aims to examine teachers’ performance in UKIN test held by LPTK (Lembaga Pendidik dan Tenaga Kependidikan/Teacherand Academic Staff College) UIN Sunan Gunung Djati. Data was collected using observation and documentation techniques. Data analysis was done using a qualitative descriptive method. The results showed that LPTK UIN Sunan Gunung Djati has provided good facilities to support the implementation of the PPG program. There are eight types of subjects tested in UKIN. There are differences in scores between classes in the UKIN test which shows variations in scores for each class with a total of 11 class intervals. The passing score for the UKIN test in 2021-2022 is 99.56%. The results of this research are expected to contribute to policy making related to the implementation of PPG in the Ministry of Religious Affairs in Indonesia.